FUNGSI RUANG HIJAU KOTA DITINJAU DARI ASPEK KEINDAHAN, KENYAMANAN, KESEHATAN DAN PENGHEMATAN ENERGI - Tri Harso Karyono (Jurnal Teknologi Lingkungan, 2005)
Town’s area needs both open and green spaces. This is not only for thesake of aesthetical requirement in shaping the town, but also to fulfill theneeds of fresher and cooler air for its inhabitants. Green area is required toaccommodate people social activities, and also to reduce air pollution –particularly in the form of carbon dioxide comes from vehicles. Besidesreducing air temperature, green area also benefit people by producing oxygenand absorbing dust. Green area must be provided adequately in the town, andbe controlled firmly by legislation. By the provision of sufficient and well-distributed green spaces in the town, people will be guaranteed to have suchlower air temperatures, fresher air and better living environment. This may beresulting, whether direct or indirectly, in reducing the consumption of energy inmany sectors in the town. This article discusses the way green space andvegetation are giving benefit to the inhabitants through several aspects asmentioned above.